Phonetic Transcription Verification with Generalized Posterior Probability - Wang, Lijuan; Zhao, Yong; Chu, Min; Soong, Frank; Cao, Zhigang (ACL/SIGPARSE, 2005)
The research of our group concerns the perception-action cycle of understanding human behaviors and generating system responses, supporting an ongoing dialogue with the user. It stems from the premise that understanding the user –by automated evaluation of speech, pose, gestures, touch, facial expressions, social behaviors, interactions with other humans, bio-physical signals and all content humans create– should inform the generation of intuitive and satisfying system responses. Our focus on understanding how and why people use interactive media contributes to making interactive systems more socially capable, safe, acceptable and fun. Evaluation of the resulting systems therefore generally focuses on the perception that the user has of them and the experience that they engender. These issues are investigated through the design, implementation, and analysis of systems across different application areas and across a variety of contexts.